Nanoconstrictions for investigating spin transfer torque effect in granular Ag–Co films. Issue 6 (12th February 2016) - Paddubrouskaya, H.; Volodin, A.; Petermann, C.; Tripathi, S.; Lagae, L.; Temst, K.; Van Haesendonck, C.
Abstract: We used lithographically fabricated nanoconstrictions made of Ag–Co granular thin films to achieve current densities above 10 7  A/cm 2 during magnetotransport measurements. Systematically measured variations of the resistance with current under high applied magnetic fields did not reveal any dramatically large magnetoresistance effect, in contrast to the previous observations using mechanical point contact based techniques. Our experimental results on resistance switching by current injection in the Ag–Co nanoconstrictions reveal spin torque effects. The switching amplitudes are considerably smaller when compared to the results obtained for pillar shaped trilayers due to the large number of Co grains in the nanoconstrictions. We demonstrate that the use of point contact patterns with nanometer dimensions, where effects resulting from current induced mechanical distortions at high magnetic fields are negligible, has obvious advantages over the mechanical point contact technique for studying spin injection effects.